Estudio de coordinación de protección de sobrecorriente del alimentador la cena perteneciente a la subestación Guanujo de la CNEL EP Bolívar - Freire Vargas, Alex Johnny (2015)
The present work was developed with the purpose to do the study of La Cena coordination of overcurrent protection feeder, the same that comes from the Guanujo substation of the Bolivar Business Unit CNEL EP and distributes the electricity service to the rural area such as: El Relleno, Las Cochas, Patococha, Rumiloma, El Castillo, Paltabamba, San Pedro del Rayo, La Cria, Candushi, Illuvi, Capilluco, El Limon, La Cena, Guachana, Santa Ana, Charquiacu, Estero Del Pescado. To develop the study, it started with the field survey of the protection elements and charge installed in the feeder which permitted to update the operating planes and to realize the analysis of the current conditions of La Cena feeder protection system, whereby it is determined that the feeder does not have a proper coordination of protections....